Deep learning the structural determinants of protein biochemical properties by comparing structural ensembles with DiffNets - Michael D. Ward (Nature Portfolio, 2021)
Comparing and contrasting structural ensembles of different protein variants helps connect specific structural features to a protein’s biochemical properties. Here, the authors propose DiffNets, a self-supervised, deep learning method that streamlines this process.